Stress experiences of healthcare assistants in family practice at the onset of the COVID-19 pandemic: a mixed methods study - Schrader, Hanna; Ruck, Jessica; Borgulya, Gábor; Parisi, Sandra; Ehlers-Mondorf, Jana; Kaduszkiewicz, Hanna; Joos, Stefanie; Grau, Anna; Linde, Klaus; Gágyor, Ildikó (Frontiers in Public Health, 2023)
At the beginning of the pandemic in 2020, healthcare assistants in general practices were confronted with numerous new challenges. The aim of the study was to investigate the stress factors of healthcare assistants in March/April 2020 as well as in the further course of the pandemic in 2020.From August to December 2020, 6300 randomly selected healthcare assistants in four German states were invited to participate in the study. We performed a mixed methods design using semi-structured hat gelöscht: h 32 hat gelöscht: g 33 hat gelöscht: p COVID-19 pandemic and HCAs' stress experiences telephone interviews and a cross-sectional survey with quantitative and open questions. The feeling of psychological burden was assessed on a 6-point likert-scale. We defined stress factors and categorized them in patient, non-patient and organizational stress factors. The results of the three data sets were compared within a triangulation protocol.1274 surveys were analyzed and 28 interviews with 34 healthcare assistants were conducted. Of the participants, 29.5% reported experiences of a very high or high feeling of psychological burden in March/April 2020. Worries about the patients' health and an uncertainty around the new disease were among the patient-related stress factors. Non-patient-related stress factors were problems with the compatibility of work and family, and the fear of infecting relatives with COVID-19. Organizational efforts and dissatisfaction with governmental pandemic management were reported as organizational stress factors. Support from the employer and team cohesion were considered as important resources.